2002
DOI: 10.1523/jneurosci.22-15-06756.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Double Dissociation within Striatum between Serial Reaction Time and Radial Maze Delayed Nonmatching Performance in Rats

Abstract: Lesions involving the intralaminar thalamic nuclei have been associated with impairments in working memory and intentional motor function in human clinical cases and animal models of amnesia. The intralaminar nuclei have afferent and efferent connections related to striatum. To test whether disruption of striatal function can account for impairments produced by intralaminar lesions, we investigated the effects of striatal lesions on two tasks known to be impaired by intralaminar damage in the rat: radial maze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 77 publications
8
47
2
Order By: Relevance
“…A two-factor (lesion group-by-RT measure) ANOVA showed a significant effect of lesion group (F (4,31) ϭ 16.526; p Ͻ 0.0001), RT measure (F (1,31) ϭ 210.338; p Ͻ 0.0001), and for the interaction of these factors (F (4,31) ϭ 5.244; p Ͻ 0.0001). This interaction is consistent with a previous report that mCPu and lCPu lesions have greater effects on choice than runway RT for a similar task (Mair et al, 2002). We explored the interaction effect by analyzing simple main effects for runway and choice RT.…”
Section: Histologysupporting
confidence: 87%
See 1 more Smart Citation
“…A two-factor (lesion group-by-RT measure) ANOVA showed a significant effect of lesion group (F (4,31) ϭ 16.526; p Ͻ 0.0001), RT measure (F (1,31) ϭ 210.338; p Ͻ 0.0001), and for the interaction of these factors (F (4,31) ϭ 5.244; p Ͻ 0.0001). This interaction is consistent with a previous report that mCPu and lCPu lesions have greater effects on choice than runway RT for a similar task (Mair et al, 2002). We explored the interaction effect by analyzing simple main effects for runway and choice RT.…”
Section: Histologysupporting
confidence: 87%
“…The VSt group effectively served as surgical controls. Previous results in our laboratory showed that VSt lesions spare the present RT task while producing substantial deficits for measures of prefrontaldependent spatial memory (Burk and Mair, 2001;Mair et al, 2002). We did not expect VSt lesions to affect any of the present RT tasks.…”
Section: Surgerycontrasting
confidence: 43%
“…The intralaminar thalamic nuclei have eVerent and afferent connections with the striatum; these connections have been shown to be important in the control of arousal and attention (Mair, Koch, Newman, Howard, & Burk, 2002). Lesions of the IML have been shown to affect striatal-dependent tasks such as the serial reaction time (SRT) task (Burk & Mair, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, the alpha-2A receptor subtype is both pre-and postsynaptically localized, while the alpha-2B and alpha-2C receptor subtypes are largely postjunctional. Both alpha-2A and alpha-2C receptors are expressed in significant amounts in the neocortical and basal ganglia structures (Renouard et al, 1994;Uhlen et al, 1997b;Winzer-Serhan et al, 1997a, b) needed for efficient working memory performance (Bailey and Mair, 2004;Chudasama and Muir, 1997;Floresco et al, 1999;Mair et al, 2002;Seamans et al, 1998). In addition, alpha-2B receptors are expressed in thalamic nuclei (Tavares et al, 1996;Winzer-Serhan and Leslie, 1997), and dorsomedial and anterior nuclei of the thalamus also contribute substantially to performance (Bailey and Mair, 2004;Floresco et al, 1999).…”
Section: Involvement Of Presynaptic Noradrenergic Mechanisms?mentioning
confidence: 99%